Control of beet and tomato damping-off by seed treatment with chitosan - Mazaro, Sérgio Miguel; Júnior, Américo Wagner; Santos, Idalmir dos; Citadin, Idemir; Possenti, Jean Carlo; Gouvêa, Alfredo de (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this study was to evaluate the effect of seed treatment using the resistance inductor chitosan to control damping-off in tomato and beet seedlings, and its relationship with plant biochemical alterations and plant protection. Each plot was represented by twenty-five seeds. Treatments consisted of seed immersion in a chitosan suspension at 0, 0.25, 0.5, 1, 2 and 4% concentrations. Seeds were then sowed in trays with a substrate infected with Rhizoctonia sp. and maintained in greenhouse conditions for 14 days. Chitosan induced seedling resistance and reduced damping-off. The 1.1 and 2.5% concentrations were more efficient in controling the damping-off for beet and tomato crops respectively. Chitosan increases the phenylalanine ammonialyase (PAL) activity and interferes with the total proteins and total and reduced sugars rates in the leaves.